Protecting Women’s Rights in Exogamous Society: Mahram in Minangkabau Customs - Agustina, Arifah Millati (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2024)
The study discusses the interpretation of mahram and the implementation of this concept in a sociological context. In Islamic jurisprudence (fiqh), mahram refers to individuals who are prohibited from marrying due to blood relations. This concept differs from exogamy, which, in the context of Minangkabau customs, refers to the prohibition of marriage between members of the same Minangkabau tribe. This prohibition is grounded not only in biological considerations but also in customary practices. Using a socio-legal approach, the researcher explored how the Minangkabau community implements the tradition of exogamy as a social rule that is deeply valued. This anthropological study included interviews with Minangkabau individuals who uphold the tradition of exogamous marriage. The researcher argues that the exogamous marriage practices of the Minangkabau people contribute to feminist fiqh because the prohibition on marriage within the same Minangkabau tribe significantly benefits women. Although the concept of mahram in Islamic jurisprudence differs from the traditional rules of the Minangkabau community, both, in practice, aim to protect women's welfare. Moreover, the Minangkabau community's mahram system is more stringent. While the concept of mahram in fiqh aims to prevent marriages among close relatives, exogamous marriage imposes stricter requirements by prohibiting marriage within the same tribe, clan, surname, or kinship group. [Artikel ini membahas konstruksi mahram di ranah sosiologis. Dalam kajian hukum Islam, mahram disebut sebagai pihak-pihak yang dilarang untuk dinikahi sebab hubungan darah. Konsep ini berbeda dengan eksogami yang dalam konteks adat Minangkabau mengandung makna keharusan menikah dengan seseorang yang berada diluar lingkup sosial suku minang. Dalam konteks adat minang, larangan menikah tidak hanya didasarkan atas pertimbangan biologis namun juga adat. Penelitian ini menggunakan pendekatan Socio-legal untuk menggali informasi tentang implementasi eksogami masyarakat Minang. Artikel ini berargumen bahwa praktik perkawinan eksogami masyarakat Minangkabau menciptakan prinsip fikih feminis, karena dengan larangan seseorang menikah dengan orang satu suku, perempuan mampu melepaskan dirinya dari sistem patriarkhi, sekaligus akan masuk dalam keluarga dengan status sosial yang lebih tinggi. Meskipun konsep mahram dalam hukum Islam berbeda dengan aturan adat masyarakat Minang, namun secara implementatif keduanya memiliki nilai yang sama yaitu kemaslahatan bagi perempuan. Bahkan, sistem mahram masyarakat adat Minang lebih ketat. Jika dalam konsep mahram pada fikih bertujuan untuk menjaga agar tidak terjadi perkawinan dengan saudara, maka perkawinan eksogami bersyarat lebih selektif, tidak membolehkan seseorang menikah dengan seseorang yang satu suku, klan, marga dan kerabat.]